2021
DOI: 10.1016/j.hroo.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Oral procainamide as pharmacological treatment of recurrent and refractory ventricular tachyarrhythmias: A single-center experience

Abstract: BACKGROUND Antiarrhythmic therapy for recurrent ventricular arrhythmias in patients who have undergone catheter ablation, and in whom amiodarone and/or beta-blockers were ineffective or contraindicated, is a controversial issue.OBJECTIVE The present study sought to evaluate the efficacy and tolerability of oral procainamide in patients with recurrent ventricular arrhythmias when the standard therapy strategy had failed.METHODS All patients treated with procainamide for recurrent ventricular tachycardia (VT) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“… 275 , 276 In a recent small single-centre observational study, oral procainamide reduced ICD therapies in patients with VT refractory to other AADs, including amiodarone. 277 However, severe side effects, including a drug-induced lupus erythematosus-like syndrome, are of concern. Of note, procainamide is not available in many countries.…”
Section: Stabilized Patientmentioning
confidence: 99%
“… 275 , 276 In a recent small single-centre observational study, oral procainamide reduced ICD therapies in patients with VT refractory to other AADs, including amiodarone. 277 However, severe side effects, including a drug-induced lupus erythematosus-like syndrome, are of concern. Of note, procainamide is not available in many countries.…”
Section: Stabilized Patientmentioning
confidence: 99%
“…Similar to its use in acute situations, procainamide has largely been studied as an AAD in patients with VT refractory to amiodarone. In this setting, a 34-patient study by Toniolo et al showed that use of procainamide after failure of previous AAD resulted in 10% reduction of ICD therapies [ 19 ]. Of note, this study has a high proportion of concomitant ablations (18 of 34 patients) that may serve as a significant confounder.…”
Section: Class I Medications: Sodium Channel Blockadementioning
confidence: 99%
“…Sotalol demonstrated early efficacy in suppression of ventricular ectopy and suppression of inducible ventricular tachyarrhythmias [ 113 , 114 , 115 ]. The relative efficacy of sotalol was unknown until the ESVEM trial compared serial efficacy of seven antiarrhythmic medications through electrophysiologic testing and Holter monitoring in patients with ventricular tachyarrhythmias [ 19 ]. Sotalol was the most frequently efficacious mediation, in 43% of patients, with the lowest rate of arrhythmia recurrence and improvement in all-cause mortality.…”
Section: Class III Medications: Potassium Channel Blockadementioning
confidence: 99%